A Child's Acute Intestinal Intussusception and Literature Review. (November 2021) - Yehouenou Tessi, Romeo Thierry; El Haddad, Siham; Oze, Koudouhonon Rita; Mohamed Traore, Wend-Yam; Dinga Ekadza, Jusly Amour; Allali, Nazik; Chat, Latifa
Acute intestinal intussusception remains a surgical emergency in infants and young children aged 3 months to 3 years. It results from the incarceration of the upstream intestinal segment in the downstream segment. In the majority of cases it is idiopathic, but can be secondary to certain pathologies notably Meckel's diverticulum. The site is most often ileo cecal. The symptomatological triad is made up of pain, vomiting, and rectal bleeding. The diagnosis is confirmed by imaging, dominated by ultrasound which remains the reference imaging. We report the case of a 3 year-old boy, followed for a malformation who presented with abdominal distension, abdominal pain, and rectal bleeding. The diagnosis of acute ileo-ileal intussusception was made. After an attempt at hydrostatic reduction under ultrasound guidance, he underwent surgical management. The postoperative period was simple and uncomplicated. Intestinal intussusception remains a pathology with a low morbidity and mortality rate of 0% to 1% due to delayed diagnosis and delayed therapeutic management.